The effectiveness of academic counseling based on a narrative approach on academic resilience and academic emotions of students with academic failure - Astereki, Mohammad amin; izadi, mahshid; Mardani Rad, Mozhgan; Zare Bahramabadi, Mehdi (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: Students experience different emotions in academic situations. Emotions are always present in educational and clinical environments. Academic resilience also refers to high levels of motivation for progress and performance, despite limited conditions. Therefore, the aim of the present study was to determine the effectiveness of teaching compassion, academic counseling based on a narrative approach, on resilience and academic emotions of students with academic failure. Methods: The research method was a semi-experimental type with a pre-test-post-test design with a control group. Using targeted sampling, 30 students from among the students with academic failure from the second grade boys’ high schools of the second period of the 12th district of Tehran were determined and randomly placed in the experimental and control groups (15 people in each group). In the pre-test and post-test stages, students responded to the academic excitement questionnaires of Pakran et al. (2002) and the academic resilience questionnaires of Martin and Marsh (2009). The academic counseling protocol based on Pine’s (2004) narrative approach was held for the experimental group for 8 sessions. Results: The results of covariance analysis showed that academic counseling training based on a narrative approach is effective on academic resilience (P=0.001 and F=19.98) and academic excitement (P=0.001 and F=34.001). Conclusion: Therefore, according to the results of the research, it is suggested that school counselors use group educational counseling trainings based on a narrative approach to control negative emotions and increase academic resilience.